A LiPF6-electrolyte-solvothermal route for the synthesis of LiF/LixPFyOz-coated Li-rich cathode materials with enhanced cycling stability. Issue 40 (4th October 2019) - Fu, Chaochao; Wang, Jiayun; Wang, Jinfeng; Meng, Linglong; Zhang, Wenming; Li, Xiaoting; Li, Liping
Abstract : A stable corrosion resistant protective layer of LiF/Li x PF y O z was in situ coated on the surface of Li-rich cathode materials to inhibit surface side reactions and thus to obtain superior cycling performance. Abstract : Li-rich layered oxide materials are promising cathode materials for lithium ion batteries because of their high capacity and low cost. Nevertheless, the lack of a stable surface structure to suppress surface side reactions and layered-to-spinel transitions and thus rapid capacity fading is a critical problem that hinders the widespread practical applications of Li-rich layered oxide materials. In this work, a stable coating layer of LiF/Li x PF y O z was introduced on the surface of Li-rich particles by a LiPF6 -electrolyte-solvothermal process followed by post-sintering treatment. In the solvothermal process, the LiPF6 -based electrolyte reacts with surface residues (such as H2 O and Li2 CO3 ) moderately at 80 °C, and then a thin LiF/Li x PF y O z protective layer is formed. The LiF/Li x PF y O z protective layer is tightly chemically bonded to the surface of Li-rich particles inhibiting surface side reactions and layered-to-spinel transitions during cycling as confirmed by d Q /d V, EIS, TEM, and XPS measurements. The obtained LiF/Li x PF y O z -coated Li-rich cathode (sample LFP4) delivers an enhanced reversible discharge capacity of 210.7 mA h g −1 at 100 mA g −1 with 90.7% capacity retention after 100 cycles, while the uncoated sample LFP0 suffers from a rapid capacity fading and the capacity retention ratio is only 75.3%. Even at a higher current density of 1000 mA g −1, the discharge capacity of LiF/Li x PF y O z -coated sample LFP4 is still as high as 188 mA h g −1 with a capacity retention ratio of 91.2% (much higher than 55.7% for uncoated sample LFP0) after 100 cycles, showing improved cycling stability and superior rate capability. This work demonstrates that LiF/Li x PF y O z coating through the LiPF6 -electrolyte-solvothermal route is a successful strategy for the modification of Li-rich oxide electrodes for the next-generation of high-energy Li-ion batteries.